Hyperlactacemia in critically ill children: comparison of traditional and Fencl-Stewart methods - Hari Kushartono; Antonius H. Pudjiadi; Susetyo Harry Purwanto; Imral Chair; Darlan Darwis; Abdul Latief (Indonesian Pediatric Society, 2007)
Background Base excess is a single variable used to quantifymetabolic component of acid base status. Several researches havecombined the traditional base excess method with the Stewartmethod for acid base physiology called as Fencl-Stewart method.Objective The purpose of the study was to compare two differentmethods in identifying hyperlactacemia in pediatric patients withcritical illness.Methods The study was performed on 43 patients admitted tothe pediatric intensive care unit of Cipto MangunkusumoHospital, Jakarta. Sodium, potassium, chloride, albumin, lactateand arterial blood gases were measured. All samples were takenfrom artery of all patients. Lactate level of >2 mEq/L was definedas abnormal. Standard base excess (SBE) was calculated fromthe standard bicarbonate derived from Henderson-Hasselbalchequation and reported on the blood gas analyzer. Base excessunmeasured anions (BE UA ) was calculated using the Fencl-Stewartmethod simplified by Story (2003). Correlation between lactatelevels in traditional and Fencl-Stewart methods were measuredby Pearson’s correlation coefficient .Results Elevated lactate levels were found in 24 (55.8%) patients.Lactate levels was more strongly correlated with BE UA (r = - 0.742,P<0.01) than with SBE (r = - 0.516, P<0.01).Conclusion Fencl-Stewart method is better than traditionalmethod in identifying patients with elevated lactate levels, so theFencl-Stewart method is suggested to use in clinical practice.